Environmental factors controlling the distribution of rhodoliths: An integrated study based on seafloor sampling, ROV and side scan sonar data, offshore the W-Pontine Archipelago. (15th October 2016) - Sañé, E.; Chiocci, F.L.; Basso, D.; Martorelli, E.
Abstract: The effects of different environmental factors controlling the distribution of different morphologies, sizes and growth forms of rhodoliths in the western Pontine Archipelago have been studied. The analysis of 231 grab samples has been integrated with 68 remotely operated vehicle (ROV) videos (22 h) and a high resolution (<1 m) side scan sonar mosaic of the seafloor surrounding the Archipelago, covering an area of approximately 460 km 2 . Living rhodoliths were collected in approximately 10% of the grab samples and observed in approximately 30% of the ROV dives. The combination of sediment sampling, video surveys and acoustic facies mapping suggested that the presence of rhodoliths can be associated to the dishomogeneous high backscatter sonar facies and high backscatter facies. Both pralines and unattached branches were found to be the most abundant morphological groups (50% and 41% of samples, respectively), whereas boxwork rhodoliths were less common, accounting only for less than 10% of the total number of samples. Pralines and boxwork rhodoliths were almost equally distributed among large (28%), medium (36%) and small sizes (36%). Pralines generally presented a fruticose growth form (49% of pralines) even if pralines with encrusting-warty (36% of pralines) or lumpy (15% of pralines) growth forms were also present. Morphologies, sizes and growth forms vary mainly along the depth gradient. Large rhodoliths with a boxwork morphology are abundant at depth, whereas unattached branches and, in general, rhodoliths with a high protuberance degree are abundant in shallow waters. The exposure to storm waves and bottom currents related to geostrofic circulation could explain the absence of rhodoliths off the eastern side of the three islands forming the Archipelago.